Sorption-enhanced steam gasification of fine coal waste for fuel producing - Nabila Aprianti; Muhammad Faizal; Muhammad Said; Subriyer Nasir (Journal of King Saud University: Engineering Sciences, 2024)
Improving the quality of syngas from fine coal waste using the sorption-enhanced gasification process is a novel technology in the production of H2. The effect of CaO on CO2 absorption and H2 increase in the steam fine coal gasification process was determined in a fixed bed gasifier. The steam gasification process took place at 650 °C using bentonite and CaO as catalysts and absorbents. Steam increased the H2 concentration in the syngas to 58 vol%. In-situ CO2 absorption is more effective with the addition of CaO. The maximum percentage of CO2 was absorbed when the Ca/C ratio 2 was 78.33 %. The H2 content in the syngas after the CO2 was absorbed increased rapidly to 75.80 vol% at a Ca-to-carbon-mole ratio (Ca/C) of 1.5 and a steam-to-feedstock ratio (S/F) of 1.5. CaO did not produce significant results for low heating value (LHV) or cold gas efficiency (CGE), with results of 12 MJ/Nm3 and 44.53 %. The dominant water gas shift reaction due to the influence of steam and CaO increased H2/CO up to 9.11, which made the syngas from this work suitable for Fischer–Tropsch synthesis.